Crystal structure of 3-chloro-5-(trifluoromethyl)pyridine-2-carboxylic acid, C7H3ClF3NO2 - Pan Xiaoru; Kong Xiang-Yan (Zeitschrift für Kristallographie - New Crystal Structures)
C7H3ClF3NO2, triclinic, P1‾ $P\overline{1}$ (no. 2), a = 5.8837(5) Å, b = 14.1634(14) Å, c = 15.3120(15) Å, α = 92.667(5)°, β = 100.364(5)°, γ = 99.475(5)°, V = 1,234.2(2) Å3, Z = 6, R gt(F) = 0.0458, wR ref(F 2) = 0.1012, T = 298 K.